IMPLEMENTATION OF CHARACTER FORMATION FOR STUDENTS THROUGH EXTRACURRICULAR ACTIVITY MANAGEMENT AT INTEGRATED ISLAMIC ELEMENTARY SCHOOL BANDAR LAMPUNG - Anisa Novita Sari; Meryati; Yetri (Esteem Journal of English Education Study Programme, 2024)
Education seeks to build students' moral character and personalities as well as their ability to collaborate with others, be responsible, autonomous, and have high moral standards. It does not merely concentrate on academic success. Participating in extracurricular activities helps students develop positive character traits. Utilizing a case study methodology and a descriptive qualitative approach, this study examines how extracurricular activities shape students' personalities and how they are managed. According to the study's findings, extracurricular activities help kids grow in their social skills, leadership, feeling of accountability, self-assurance, and academic prowess. The purpose of evaluating extracurricular activities is to find out how well they help kids develop desirable character traits. It is possible to develop extracurricular activities by offering a greater range of options, encouraging student participation in the planning and execution process, training managers, and providing suitable infrastructure and facilities. Good extracurricular activity management is essential to developing students' good character traits and equipping them for life's difficulties.